Computer Control System Application for Electrical Engineering and Electrical Automation - Liu, Weigang (IOP conference series. Materials Science and Engineering, 2018)
Electrical engineering has gradually entered the era of automation technology along with the development of high technology. In computer control systems, the application of automation technology and electrical engineering has gradually improved. The paper mainly discusses the basic concepts of intelligent technology and electrical automation, and focuses on the specific application of intelligent computer control in electrical automation, and analyzes the application prospect and development trend of this technology in electrical engineering in the future.